Prefiks derivasi pembentuk verba bahasa Jerman dalam Kinderroman "Emil und die Detektive" karya Erich Kästner - Sawitri, Wulan; Megawati, Sri (Journal of Culture, Literature and Foreign Language Teaching, 2025)
This study aims to describe: (1) the derivational prefixes forming verbs in the German language and (2) their meanings in the children’s novel Emil und Die Detektive by Erich Kästner. This research is a qualitative descriptive study. The subject of this research is the children’s novel Emil und Die Detektive by Erich Kästner. The object of the research consists of all the German verbs in the novel. Data collection was conducted using the observation method with free conversation observation (SBLC) and note-taking techniques. Data analysis was performed using the distribution method with direct element division (BUL) and marking reading, as well as the comparison method with determining element classification (PUP). Reliability testing was conducted using intrarater and interrater techniques. The results of this study indicate that 281 data points of derivational prefixes forming German verbs were found in the children’s novel Emil und Die Detektive by Erich Kästner, including 28 data points of derivational prefixes based on nouns (15 data of functional derivation and 13 data of transpositional), 207 data point based on verbs (154 data of expansion and 53 data of modification), and 46 data points based on adjectives (33 data of functional derivation and 13 data of transpositional).